Holistic strategy for preserving Sundanese dance digitally: Digitization, intelectual property rights, sustainable cultural regeneration - Khadijah, Ute Lies Siti; Pamungkas, Kasno; Rafianti, Laina; Lusiana, Elnovani; Bifakhlina, Febriyanti (Faculty of Communication, Padjadjaran University, 2026)
Background: Sundanese traditional dance is an intangible cultural heritage that carries historical memory, embodied knowledge, aesthetic values, and collective identity. In the contemporary digital environment, this heritage faces intertwined challenges: declining regeneration among young people, weak documentation practices, limited digital capacity in community-based studios, and legal vulnerability caused by incomplete intellectual property protection. Purpose: This study aims to formulate and evaluate a holistic preservation strategy for Sundanese traditional dance by integrating digital archiving, community capacity building, intellectual property protection, and cultural sustainability planning. Methods: The study employed Community Action Research with Azka Studio Dance Community in Rancaekek, Bandung Regency. Data were collected through field observation, interviews with studio managers and participants, documentation studies, training records, metadata compilation, and reflective evaluation. The intervention was organized into four connected stages: diagnosing preservation gaps, planning community-based actions, implementing digitization and legal-literacy activities, and evaluating sustainability outcomes. Results: The intervention achieved the main targeted outputs: ten dance works were documented in high-definition video and described using cultural metadata; eight young digital cadres were trained to manage documentation workflows; thirty youths participated in dance regeneration activities; twenty artists received intellectual property training; five dance works were prepared for copyright registration; and digital dissemination through social media increased public visibility. Conclusion: The study demonstrates that preservation of intangible cultural heritage requires more than recording performances. A sustainable model depends on the integration of archival standards, community participation, legal awareness, and regeneration mechanisms. For Library and Information Science, the case contributes a practical model of community-based digital cultural archiving that connects documentation, metadata, access, rights management, and long-term stewardship.